KRISIS DAN TRANSISI KARIR ORANG DEWASA MENURUT SUPER DAN PERSPEKTIF ISLAM - Fatheni Cova Kamil Khairy; Syahrepah Syahrepah; Adella Suryani Putri; Masril Masril (STKIP Pesisir Selatan, 2026)
This study aims to examine career crises and transitions in adulthood based on Donald Super's career theory and an Islamic perspective. The method used in this study is a literature review by collecting and analyzing various scientific sources in the form of books, journals, and related documents. The results of the study indicate that career is a lifelong development process influenced by self-concept, internal factors, and external factors of the individual. According to Super, in adulthood, individuals are in the formation and maintenance stage, vulnerable to career crises and transitions due to changes in life roles, job demands, technological developments, and mismatches between career expectations and reality. Career crises can cause stress, anxiety, identity confusion, and decreased motivation, but can also be an opportunity for self-development. From an Islamic perspective, career is seen as a form of worship and a trust that must be carried out responsibly. Spiritual values ​​such as patience, gratitude, ikhtiar, and tawakkul play an important role in helping individuals face career crises and transitions. Islamic career counseling is a relevant approach to help individuals understand themselves, make appropriate career decisions, and achieve a balance between worldly success and spiritual happiness.